2009
DOI: 10.1111/j.1530-0277.2009.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Mood‐Related Drinking Motives Mediate the Familial Association Between Major Depression and Alcohol Dependence

Abstract: Background-Major depression and alcohol dependence co-occur within individuals and families to a higher than expected degree. This study investigated whether mood-related drinking motives mediate the association between major depression and alcohol dependence, and what the genetic and environmental bases are for this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 68 publications
(74 reference statements)
6
45
0
1
Order By: Relevance
“…Family history of AUDs is known to confer high risk for mood disorders, and mood disorders may lead to AUDs (9, 3537). For instance, Young-Wolff and colleagues' (38) finding that the use of alcohol to improve mood mediated the relationship between depression and AUDs provides support for the “self-medication” hypothesis. The development of AUDs among individuals with mood disorders may in some cases be the result of chronic alcohol use to suppress mood disorder symptomology (3941).…”
Section: Introductionmentioning
confidence: 99%
“…Family history of AUDs is known to confer high risk for mood disorders, and mood disorders may lead to AUDs (9, 3537). For instance, Young-Wolff and colleagues' (38) finding that the use of alcohol to improve mood mediated the relationship between depression and AUDs provides support for the “self-medication” hypothesis. The development of AUDs among individuals with mood disorders may in some cases be the result of chronic alcohol use to suppress mood disorder symptomology (3941).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a sample of 5,000 adults age 30 and older, Young-Wolff, Kendler, Sintov, and Prescott (2009) revealed that familial factors underlying drinking to manage mood accounted for essentially all of the genetic and common environmental overlap of mood disorder and alcohol dependence. Although coping motives might be tied similarly to depression and other distressing emotions caused or exacerbated by withdrawal symptoms from substance use, these motives could also be etiologically significant in that they signal a more primary predisposition toward mood disorders and substance abuse.…”
Section: Implications For Comorbidity Theory and Researchmentioning
confidence: 98%
“…After the purpose of this research procedure has been explained, the person who will be interviewed must be informed that this phone call will be recorded. The objectives of the study will be explained, specifying the approximate duration of the interaction [7,13 ]. Authorization to participate in the study will be documented by recording this telephone interaction and could be transcribed for filing purposes.…”
Section: Interviews By Telephonementioning
confidence: 99%
“…The Informed Consent Form is signed and dated before the participant begins any research activity. This is the process most widely used to obtain consent in research settings [4][5][6][7].…”
Section: Usual Informed Consent Processmentioning
confidence: 99%